2000
DOI: 10.1046/j.1440-1681.2000.03362.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Tachykinins On Uterine Smooth Muscle

Abstract: 1. Sensory nerves supplying the mammalian uterus have been shown to contain substance P (SP) and neurokinin (NK)A. This review presents some of the advances that have led to a greater understanding of the effects of tachykinins on uterine smooth muscle. 2. The cell-surface peptidase neprilysin (EC.3 24.11, endopeptidase 24.11, enkephalinase, CALLA, CD10) has been shown to play a major role in regulating the actions of tachykinins on both rat and human myometrium. Because this peptidase is known to be regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 85 publications
(95 reference statements)
1
28
0
Order By: Relevance
“…For many years, the tachykinins were considered almost exclusively as peptides of neuronal origin. NKB is present in the central nervous system and the spinal cord (Kangawa et al, 1983;Moussaoui et al, 1992;Goubillon et al, 2000;Patacchini et al, 2000) while SP and NKA are found in the central nervous system and also in primary afferent sensory neurons supplying a number of peripheral tissues (Holzer, 1988;Maggi and Meli, 1988;Lundberg, 1996;Patak et al, 2000a). SP and NKA are released from nerve endings at both the spinal cord and the peripheral level and play a role as excitatory neurotransmitters (Lembeck and Holzer, 1979;Maggi, 1991;Otsuka and Yoshioka, 1993;Meini and Maggi, 1994;Patacchini et al, 1998, Patak et al, 2000a.…”
Section: Introductionmentioning
confidence: 99%
“…For many years, the tachykinins were considered almost exclusively as peptides of neuronal origin. NKB is present in the central nervous system and the spinal cord (Kangawa et al, 1983;Moussaoui et al, 1992;Goubillon et al, 2000;Patacchini et al, 2000) while SP and NKA are found in the central nervous system and also in primary afferent sensory neurons supplying a number of peripheral tissues (Holzer, 1988;Maggi and Meli, 1988;Lundberg, 1996;Patak et al, 2000a). SP and NKA are released from nerve endings at both the spinal cord and the peripheral level and play a role as excitatory neurotransmitters (Lembeck and Holzer, 1979;Maggi, 1991;Otsuka and Yoshioka, 1993;Meini and Maggi, 1994;Patacchini et al, 1998, Patak et al, 2000a.…”
Section: Introductionmentioning
confidence: 99%
“…For many years, the tachykinins were considered almost exclusively as peptides of neuronal origin. SP and NKA are found in the central nervous supplying a number of peripheral tissues [1,2]. SP and NKA are released from nerve ending at both the spinal cord and the peripheral level and play a role as excitatory neurotransmitters [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the majority of molecular (Pinto et al, 1999;Candenas et al, 2001), immunohistochemical (Traurig et al, 1984;Papka et al, 1985) and functional (Fisher et al, 1993;Pennefather et al, 1993b;Fisher & Pennefather, 1997;Magraner et al, 1998;Patak et al, 2000a) studies of the uterine distribution of tachykinins, tachykinin receptors and/or degradation of tachykinins have been conducted using the rat. It is now emerging, however, that there are species (Patak et al, 2000a, b;2002a) as well as hormonal-and pregnancyrelated differences in tachykinin expression and actions in the mammalian myometrium (Pinto et al, 1999;Candenas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%